(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
Libya is a developing country and it has a unique culture, as any other country, with a significant position as the second largest oil producer in Africa. It has experienced dynamic changes over a short period of time. The aim of this study is to investigate the collapse of Gadhafis regime in Libya has opened up space for new regional tensions over greater economic power and political representation, with hydrocarbon resources often used as a bargaining chip. There have been severe tensions surrounding the possible relocation of the headquarters of the National Oil Corporation (NOC) from Tripoli to Benghazi. The excessive oil profits are being taken away by foreign oil companies. Apart from that the foreign oil companies collude with corrupt government officials to disobey environmental laws. In the light of these problems, the thesis argued that Libyas oil resource is nothing but a curse and not a blessing. The situation has gone from bad to worse because too much emphasis has been placed on long term measures instead of short-term solutions. This is not more than scratching the surface while the substance of the problem is left untouched. To achieve the aim and particular objectives of the study it was necessary to utilize more than one research method. Firstly, a descriptive method is used to provide an overview of accounting and its environment in a developing country, and the economic, social and political environment in Libya. Secondly, we choose John Rawls method of justice because it is designed to provide proposals which people cannot reasonable reject if they are committed to advance the welfare of everyone. In particular, it seeks to map the current idea which will be to develop short-term measures that no member of the current conflicts can reasonably object. The content analysis showed that the Libyan government can approach the Eastern Libya oil crisis in a short-term course. The study argued that short-term justice will help to provide the immediate needs of tens of millions of neglected and impoverished citizens of Eastern Libya region in the meantime while the government continue to work on long-term solutions to her problems. The findings from the method of justice as propounded by John Rawls to produce specific short-term solutions that will solve the problem of economic injustice, political marginalization, social conflicts, and revenue distribution imbroglio.